Measuring students' generic skills through national assessment - Makhshun, Toha; A'la, Bassam Abul; Kusaeri, Kusaeri (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2023)
This study aims to measure the generic skills (GS) of Madrasah Aliyah (MA) students in Indonesia. Respondents who participated in this study were madrasah students scattered in East Java and Central Java as representatives of MAs in Indonesia. The method used in this research is a survey distributed via Google Form. Three dimensions are mentioned in the research instrument for measuring GS: religious moderation, critical and creative thinking skills, and interpersonal skills. Using SPPS version 16 software, a descriptive analysis was employed as the data analysis technique. The results of this study showed that the GS of students with religious moderation indicators obtained the highest average of 54.03% on the Likert scale 4. Critical and creative thinking skills indicators obtained the highest average results, 67.99%, on the Likert scale 4. The indicator of interpersonal skill obtained the highest average of 55.88% on the Likert 4 scale. Hence, it is expected of educational institutions to implement policies to enhance the GS of MA students, particularly in creating a more student-oriented learning model, also known as student-centered learning.